Climate change is likely to increase the development rate of anthelmintic resistance in equine cyathostomins in New Zealand. (December 2020) - Sauermann, Christian W.; Leathwick, Dave M.; Lieffering, Mark; Nielsen, Martin K.
Abstract: Climate change is likely to influence livestock production by increasing the prevalence of diseases, including parasites. The traditional practice of controlling nematodes in livestock by the application of anthelmintics is, however, increasingly compromised by the development of resistance to these drugs in parasite populations. This study used a previously developed simulation model of the entire equine cyathostomin lifecycle to investigate the effect a changing climate would have on the development of anthelmintic resistance. Climate data from six General Circulation Models based on four different Representative Concentration Pathways was available for three New Zealand locations. These projections were used to estimate the time resistance will take to develop in the middle (2040–49) and by the end (2090–99) of the century in relation to current (2006–15) conditions under two treatment scenarios of either two or six yearly whole-herd anthelmintic treatments. To facilitate comparison, a scenario without any treatments was included as a baseline. In addition, the size of the infective and parasitic stage nematode population during the third simulation year were estimated. The development of resistance varied between locations, time periods and anthelmintic treatment strategies. In general, the simulations indicated a more rapid development of resistance under future climates coinciding with an increase in the numbers of infective larvae on pasture and encysted parasitic stages. This was especially obvious when climate changes resulted in a longer period suitable for development of free-living parasite stages. A longer period suitable for larval development resulted in an increase in the average size of the parasite population with a larger contribution from eggs passed by resistant worms surviving the anthelmintic treatments. It is projected that climate change will decrease the ability to control livestock parasites by means of anthelmintic treatments and non-drug related strategies will become increasingly important for sustainable parasite control. Graphical abstract: Image 1 Highlights: The development of anthelmintic resistance under climate change was simulated. Climate can become more suitable for parasite development, increasing population size. The time resistance took to develop was linked to changes in parasite population size. Non-drug related strategies will become increasingly important for parasite control.